Penerapan Metode Forward Chaining Pada Sistem Pakar Untuk Diagnosa Kerusakan Sepeda Motor Berbasis Web - Mhd Ilyas; Jhonson Efendi Hutagalung; Suparmadi Suparmadi (Forum Kerjasama Pendidikan Tinggi, 2022)
Repair motorbikes in the workshop, there are still some beginner technicians who do not really understand looking for damage to motorbikes so they have to ask senior technicians at the workshop often. For this reason, it is necessary how to diagnose damage to motorcycle vehicles by knowing the types of damage, symptoms of damage, characteristics of damage, then diagnosis and alternative solutions to problems are needed. Most of the damage to motorbikes occurs due to negligence in carrying out maintenance on the motorbike itself, whether it is due to the busyness of the user or lack of knowledge in the maintenance of the motorbike used. The inference model used in making this expert system is forward chaining, while the search technique uses depth first search. Determination in diagnosing expert systems is done through a consultation process between the system and the user. In system testing, the results obtained are ECU System malfunction based on novice technician answers to system questions. By using the IF-THEN rule to obtain a solution for motorcycle damage